Traditional Case Management Is a Commodity: Mobility, Analytics, and Interoperability drive better Outcomes. - Venzke, Stuart; Jones, Mary-Sara; Dommel, Paul (Policy & Practice (19426828), 2018)
The article discusses the three key capabilities supported by information technology that health and human service (H/HS) agencies should focus on when building a modern and responsive H/HS system. Topics covered include how case management systems can help improve efficiency and consistency across an agency, the advantages of an interoperable H/HS system, and how interoperability, analytics, and mobility have made it possible for innovative H/HS leaders to provide service.